Corpus analysis of metadiscourse in undergraduate academic projects / Noorzan Mohd Noor and Amaal Fadhlini Mohamed Alam - Mohd Noor, Noorzan; Mohamed Alam, Amaal Fadhlini (Universiti Teknologi MARA Shah Alam, 2017)
Writers engage different types of metadiscourse markers in interacting with the readers. They provide indicators in their writing of the contents to help readers comprehend and respond to the text. This paper is a preliminary study to identify types and categories of metadiscourse found in a corpus of undergraduate academic projects (UAP corpus). This study is significant as it identifies types and categories of metadiscourse found in both good and weak undergraduate academic writing. Hence, this study is relevant to further support related research on the use of metadiscourse among tertiary level students to write effectively in academic writing. Since metadiscourse has never been directly taught as a subject to undergraduate students, it may contribute to the lack of awareness on metadiscourse functions in effective writing. In this study, the metadiscourse items in UAP corpus are identified and rated by inter-raters. It is a corpus-based research study that involves collecting, analyzing, and using qualitative and quantitative approaches to identify metadiscourse items in the corpus.